Social life in the territory of the three cities during Roman era - Abdulqdir, Suad Mohammed Meelad; nor, Mohd Roslan Mohd; Abdul Hamid, Faisal Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2017)
The geographical location of Libya in general, and the three cities (Sabratha - Lebda - Aya) in particular have an important role in the region to have close links with the peoples of the ancient world, especially with the Romans, which made these cities affected by the cultures and peoples of these peoples’ That the region witnessed in the Roman era a remarkable development in many aspects of life, because it contains elements to qualify for any cultural activity. Therefore, the study of the social history of the Libyan tribes on different historical stages, is very important in that they reveal the most important aspects of their lifestyle.In his study, the researcher studied the inductive method in monitoring the relevant information, and then analyzed it carefully according to the comparative approach between the nature of the Roman presence and other people who came to the region. By tracing the family’s social order in the Roman period, there were significant differences between the two cultures. "The local population had some habits and kept them" and added to them what suited their own lives